2021
DOI: 10.1186/s12905-021-01273-w
|View full text |Cite
|
Sign up to set email alerts
|

Workplace gender-based violence and associated factors among university women in Enugu, South-East Nigeria: an institutional-based cross-sectional study

Abstract: Background Exposure to workplace gender-based violence (GBV) can affect women's mental and physical health and work productivity in higher educational settings. Therefore, this study aimed to examine the prevalence of GBV (workplace incivility, bullying, sexual harassment), and associated factors among Nigerian university women. Methods The study was an institutional-based cross-sectional survey. The multi-stage sampling technique was used to selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…Risk factors for perpetration, including individual, relationship, community, and social factors, were measured based on the variables found through a detailed literature review [ 19 21 ]. Accordingly, six questions were used to assess sexual violence in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Risk factors for perpetration, including individual, relationship, community, and social factors, were measured based on the variables found through a detailed literature review [ 19 21 ]. Accordingly, six questions were used to assess sexual violence in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, in light of the aforementioned experiences, the organization must have clear rules and directives to handle it. Nevertheless, even when rules exist, workers and supervisors may be unaware of them or lack enough training on policy requirements (Agbaje et al, 2021). Therefore, gender-disaggregated data collection and strict monitoring of these regulations may be conducted to guarantee that these concerns are addressed.…”
Section: )mentioning
confidence: 99%
“…Therefore, carrying out a study on the impact of sexual harassment on the over-all well-being of female senior non-teaching workers of public tertiary institutions should normally be a desirable inquiry. Agbaje et al (2021) conducted a study on workplace gender-based violence and associated factors among university women in Enugu, South-East, Nigeria. The study confirmed high prevalence of sexual harassment among university women in Enugu, Nigeria.…”
mentioning
confidence: 99%
“…In addition, power imbalance which predisposes female workers to sexual coercion arising from offer of bonuses and promotions in return for sexual attention is a major factor encouraging sexual harassment in the university environment. To curb this menace, Agbaje et al (2021) suggested an urgent need for well-functioning support structures for sexual harassment victims and active organizational structures in higher educational settings. Bondestam and Lundgvist (2020) in their study on sexual harassment in higher education suggested an egalitarian workplace that will ensure power balance and equality among all workers irrespective of their gender.…”
mentioning
confidence: 99%
See 1 more Smart Citation